Resiliensi melalui Strategi Koping dalam Pencegahan dan Penanganan Adiksi pada Remaja Generasi Z di SMA ”X” DKI Jakarta - Christina Lumbantoruan; Jessica Cecilia; Nisrina Rania (Humanitas (Jurnal Psikologi), 2026)
Substance addiction and behavioral addiction have become increasingly concerning issues among Generation Z adolescents growing up in the digital era with expansive access to information. Exposure to these forms of addiction not only disrupts academic performance but also affects emotional regulation and social functioning. This study aims to describe adolescent resilience through coping strategies used to prevent and manage addictive behaviors. This research employed a descriptive quantitative approach involving 150 high school students in DKI Jakarta, using descriptive statistical analysis and the Chi-Square test to identify the focus and effectiveness of coping strategies. The findings indicate that the most dominant coping strategy was problem-focused coping, characterized by behavioral and environmental changes (49%), followed by emotion-focused coping in the form of self-awareness and self-commitment (24%). Chi-Square analysis showed that participants generally demonstrated adaptive coping strategies. Pure maladaptive coping strategies were found only among male students, with a proportion of approximately 1%. These findings highlight the need to strengthen internal resources in adolescents. Recommendations include school- and community-based psychoeducation, emotional regulation training, and cognitive-behavioral interventions. Future research is encouraged to use mixed-method and correlational approaches to explore coping patterns more deeply across time.